Computational Geometry, Graphs and Applications 9th International Conference, CGGA 2010, Dalian, China, November 3-6, 2010, Revised Selected Papers - Akiyama, Jin.; Bo, Jiang; Kano, Mikio; Tan, Xuehou; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-conference proceedings of the China-Japan Joint Conference on Computational Geometry, Graphs and Applications, CGGA 2010, held in Dalian, China, in November 2010. The 23 revised full papers presented were carefully selected during two rounds of reviewing and improvement from numerous submissions. All aspects of computational and discrete geometry, graph theory, graph algorithms, and their applications are covered.
Keywords: Computer science; Data structures (Computer science).; Computer software; Computational complexity; Computer graphics; Algorithms; Discrete groups; Computer Science; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science; Computer Graphics; Data Structures; Convex and Discrete Geometry; Algorithms